232 TRENDS IN HEPATOCELLULAR CARCINOMA IN NEW MEXICO, 1973-2002. Issue 1 (1st January 2007) - DiLauro, S.; Dunkelberg, J.; Wiggins, C.; Patt, Y.
Abstract : Background: There is marked geographic and ethnic variation in the incidence hepatocellular carcinoma (HCC) worldwide. Although the United States as a whole is considered a region of lower incidence, the number of HCC cases in this country has doubled over the last two decades. The epidemiology of HCC in the heterogeneous state population of New Mexico has not been previously examined. New Mexico has a population that is 10.2% Native American, 40.4% Hispanic, and 45.7% non-Hispanic white. Methods: We used data from the population-based New Mexico Tumor Registry to characterize temporal patterns in incidence rates of HCC among New Mexico's American Indian, Hispanic, and non-Hispanic white population during the 30-year period, 1973-2002. Average annual age-adjusted incidence rates were calculated by the direct method using the US 2000 standard population. Results: There was little race/ethnic variation in incidence rates in New Mexico early in the study period (1973-1977). However, the rate of increase among both Hispanic and American Indian males far outpaced increases among non-Hispanic whites beginning in the 1980s; by the end of the study period in 2002, incidence rates of HCC among American Indian (10.8 per 100, 000) and Hispanic males (10.8) were nearly three times higher than those of non-Hispanic whites (3.7). Similar trends were observed among Hispanic and non-Hispanic white females, although the magnitude of change in incidence rates was much lower among women than men. A relatively small number of cases of disease among American Indian females constrained interpretation of temporal trends in this group. conclusions: Our population-based data show profound ethnic differences in HCC incidence rate trends in New Mexico's American Indians, Hispanics, and non-Hispanic whites. Further studies are warranted to characterize the distribution of risk factors that contributed to these disparate increases in disease in New Mexico.